Duality for Semi-Infinite Minimax Fractional Programming Problem Involving Higher-Order (Φ, ρ)-V-Invexity. (3rd July 2017) - Stancu-Minasian, I. M.; Kummari, Krishna; Jayswal, Anurag
ABSTRACT: In this paper, we introduce the concept of higher-order ( Φ, ρ )- V -invexity and present two types of higher-order dual models for a semi-infinite minimax fractional programming problem. Weak, strong, and strict converse duality theorems are discussed under the assumptions of higher-order ( Φ, ρ )- V -invexity to establish a relation between the primal and dual problems.